Land use alters diazotroph community structure by regulating bacterivores in Mollisols in Northeast China - Zhang, Zhiming; Han, Xiaozeng; Pan, Fengjuan; Liu, Hang; Yan, Jun; Zou, Wenxiu; McLaughlin, Neil B.; Hao, Xiangxiang (Frontiers in Microbiology, 2022)
Changes in land use can generate environmental pressures that influence soil biodiversity, and numerous studies have examined the influences of land use on the soil microbial communities. However, little is known about the effects of land use on ecological interactions of soil microbes and their predators. Diazotrophs are key soil microbes that play important functional roles in fixing atmospheric nitrogen. In this study, we investigated the co-association of diazotroph community members and patterns of diazotroph and bacterivore networks under different long-term land uses including cropland, grassland, and bare land. Diazotroph community was characterized by high-throughput sequencing. The results indicated that land use type influenced the dominant genera of diazotrophs and shaped the occurrence of specific indicator diazotroph taxa. Co-existing pattern analysis of diazotrophs and bacterivores indicated that grassland converted from cropland increased the complexity of diazotroph and bacterivore network structure. The number of nodes for diazotrophs and bacterivores was higher in grassland than in cropland and bare land. Random forest analysis revealed that six bacterivore genera Cephalobus, Protorhabditis, Acrobeloides, Mesorhabditis, Anaplectus, and Monhystera had significant effects on diazotrophs. Bacterivores were found to have predominantly negative effects in bare land. Different bacterivores had differing effects with respect to driving changes in diazotroph community structure. Structural equation model showed that land use could control diazotroph community composition by altering soil properties and regulating abundance of bacterivores. These findings accordingly enhance our current understanding of mechanisms underlying the influence of land use patterns on diazotrophs from the perspective of soil food webs.